Abstract as a form of scientific text compression (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article investigates actual problems of methods in teaching Ukrainian among foreign students. Ability to perform text compression is essential in comprehensing educational and scientific literature devoted to chosen specialty. Annotation is a kind of such activities. The author analyzes annotation types and offers a system of ways that will help skill formation in writing annotations to texts of different types.
Keywords: abstract; annotation writing algorithm; microtext; text compression; standard linguistic annotation units